Mitomycin-C-treated peripheral blood mononuclear cells (PBMCs) prolong allograft survival in composite tissue allotransplantation - Radu, Christian Andreas; Kiefer, Jurij; Horn, Dominik; Kleist, Christian; Dittmar, Laura; Şandra-Petrescu, Flavius Ionuţ; Ryssel, Henning; Köllensperger, Eva; Gebhard, Martha-Maria; Lehnhardt, Marcus; Germann, Günter; Terness, Peter (Journal of surgical research, 2012)
Background: Composite tissue allotransplantation (CTA) was introduced as a potential treatment for complex reconstructive procedures and has become a clinical reality. Hand and face transplantation, the most widely recognized forms of CTA, have intensified immunological research in this emerging field of transplantation. Mitomycin C (MMC) is an alkylating agent that suppresses allogeneic T-cell responses. MMC-treated dendritic cells/PBMCs have been shown to induce donor-specific tolerance in solid organ allograft transplantations. Methods: Fully mismatched rats were used as hind limb donors [Lewis (RT11)] and recipients [Brown-Norway (RT1n)]. Fifty-five allogeneic hind limb transplantations were accomplished in six groups. Group A (n = 10) received donor-derived MMC-treated PBMCs on transplantation day. Group B (n = 10) rats received no immunosuppression, group C (n = 10) received FK506 and prednisolon, group D consisted in isograft transplantation without immunosuppression, group E (n = 10) received non-treated PBMCs, and group F (n = 5) received PBS without any donor-derived cells. Rejection was assessed clinically and histologically. Results: In group A, the survival times of the allografts were prolonged to an average of 8.0 d. Rejection was significantly delayed compared with the averages of the corresponding control groups B, E, and F (5.5, 5.9, and 5.8 d). No rejection was seen in control groups C and D. Conclusion: These results demonstrate that MMC-treated donor PBMCs significantly prolong allograft survival when administered systemically on the day of transplantation. However, the immunomodulatory effect is relatively modest with further research being required to clarify dose-effect relations, cell characteristics, and an optimized mechanism and timing for cell application.